2018
DOI: 10.1002/jor.23888
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage‐derived inflammatory cytokines regulate growth factors and pain‐related molecules in mice with intervertebral disc injury

Abstract: Upregulation of inflammatory cytokines and various growth factors is a significant contributor to discogenic low back pain. The aim of this study was to investigate possible regulation of pain-related molecules by macrophages and the role of macrophage-derived molecules in injured intervertebral disc (IVD)s. C57BL/6J mice were used in this study. We characterized the expression profiles of genes for tumor necrosis factor (TNF)-alpha, interleukin (IL)-1beta, nerve growth factor (NGF), and vascular endothelial g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 28 publications
3
44
0
Order By: Relevance
“…Macrophage‐like cells in discs play an important role in IVD pathology, including disc degeneration and pain, in both the acute and chronic phases . CCL2 protein expression in the acute phase was consistent with M1 and M2a macrophage marker expression.…”
Section: Discussionmentioning
confidence: 63%
See 4 more Smart Citations
“…Macrophage‐like cells in discs play an important role in IVD pathology, including disc degeneration and pain, in both the acute and chronic phases . CCL2 protein expression in the acute phase was consistent with M1 and M2a macrophage marker expression.…”
Section: Discussionmentioning
confidence: 63%
“…However, the increase in the percentage of macrophages persisted up until day 28, with M2c macrophages, according to Cd206 expression, in particular being significantly elevated in the later phase. Recent studies have suggested that both M1 and M2 macrophages exist in human and mouse discs and contribute to the IVD pathology . M1 macrophages induce inflammatory conditions via the production of inflammatory mediators .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations